Who Cares About Wildlife? Social Science Concepts for Exploring Human-Wildlife Relationships and Conservation Issues - Manfredo, Michael J. (Springer New York : Imprint: Springer, 2008)
Wildlife holds a special place in the human consciousness. It is a source of attraction and fear, material value and symbolic meaning, religious or spiritual significance, and it is a barometer of people's concern for environmental sustainability. Why do humans care so much about wildlife? In Who Cares About Wildlife?, author Michael J. Manfredo explores that question through multiple social science perspectives. How has evolution prepared human responses to wildlife? How can we better understand the nature of our cognitive and emotional responses to wildlife? And how can we place those responses in a broad cultural context? A theoretical perspective is advanced that draws upon these multiple perspectives and that proposes the rise of caring and mutualism values in post-industrial society. Directions for future research and managerial implications are interwoven into this theoretical overview. "This ambitious book concerning the human dimensions of wildlife management comes at an opportune time as global warming threatens extinction of large numbers of species. After considering the biological bases of human-wildlife interaction, Manfredo reviews and applies major social science theories and research to wildlife management. Chapter by chapter, the author introduces the reader to a central construct or theoretical approach and considers its implications for wildlife management. In this manner, the book ranges widely, from emotions, attitudes and social norms, to values and culture. Though necessarily brief, the literature reviews are informative and up-to-date, and their relevance for wildlife management is made clear by numerous examples and illustrative case studies. This engaging book is essential reading for students and professionals interested in research on the human dimensions of wildlife management." - Icek Aizen, Professor and Head, Division of Social Psychology, University of Massachusetts- Amherst.